Brain compatible teaching and learning in the foreign language classroom: teachers' voices - Wagner-Heaston, Melitta, author; Lehmann, Jean P., advisor; Banning, James H., committee member; Richburg, Robert W., committee member; Hughes, Jolyon T., committee member (Colorado State University. Libraries, 2006)
The purpose of this qualitative study is to discover foreign language teachers' perceptions of brain-based teaching and learning and how these principles affect student learning. To gain an understanding, examine, and describe these teachers' experiences with brain-compatible teaching and learning. While some research has been directed toward second language acquisition and brain-based teaching and learning little has focused on the phenomenon of what foreign language teachers' experience has been with these principles. This study included a qualitative research design in the phenomenological tradition. Seven K-12 foreign language teachers, familiar with brain-based teaching and learning, from throughout the state of Colorado were interviewed. In this study the terms brain-based teaching and learning is also referred to as brain-friendly or brain-compatible. Based on the four main research questions, ten themes were identified in the study. These included how learning happens, teacher and learner responsibility, connecting teaching and learning, active learning, internalizing learning, countering student apathy, fun versus fear, instilling love of language, and promoting success. Two essence themes emerged from the teachers' interviews. The essence of their experiences communicated itself as a bond between teacher-student engagement and the setting of the life experience that is their connection. This hybrid model of covenant and context formed the framework through which effective teaching and learning could be realized. In a shared understanding teacher and learner form a learning system where deeper learning occurs. The nature of the experience is reflected in how teacher and student relate and interact with one another which is the covenant. The quality of the experience centered on the context. The context includes environment, structure and relevancy. This synergistic approach to effective second language learning is supported by the principles of brain-based theory on how one learns. Much the way neural networks work together to form a memory network, the covenant and context model describes how the understanding and actions of people working together increase overall effectiveness. Based on the findings in this study, additional research in the realm of brain-based teaching and learning and second language acquisition is needed. Further examination of brain-based principles as they relate to foreign language pedagogy at different levels of instruction is also warranted. This study provides a basis for future research that should establish ways to place brain-based teaching and learning principles into foreign language education practice. In an effort to increase effectiveness of teaching and learning in second language classrooms, foreign language methods courses in teacher education programs may benefit from the findings in this study. Increased awareness and visibility of how the brain learns and how instruction should be structured is critical to effective learning.
Keywords: multicultural education; teacher education; educational psychology